Autoimmunity: from physiology to pathology. Natural antibodies, mucosal immunity and development of B cell repertoire - Tlaskalová-Hogenová, H; Mandel, L; Stĕpánková, R; Bártová, J; Barot, R; Leclerc, M; Kovárů, F; Trebichavský, I (Folia biologica, 1992)
Presence of spontaneously produced immunoglobulins bearing a broad spectrum of "natural" antibody specificities (including autoantibodies) in sera and other body fluids results mainly from inapparent immunization and polyclonal B cell activation by microflora and food antigens occurring mostly on mucosal surfaces. Early postnatal ontogeny in external environment is characterized by rapid growth and functional maturation of secondary lymphatic tissues as a consequence of this "natural" mucosal immunization. Under normal circumstances a state of "oral" tolerance to intestinal antigens is actively established after this period. Studies performed in germ-free, antigen-free and maternal antibody-deprived animals showed that low amounts of natural antibodies (mainly of IgM isotype) are formed without any known cause of stimulation. These "nonstimulated" antibodies, similarly as hybridomas originating from nonimmunized newborns, correspond to the preimmune repertoire of antibodies characterized by poly-specificity, high connectivity and reactivity against self antigens. Together with other innate humoral and cellular factors, they probably represent the first line of anti-infectious resistance. Moreover, due to their connectivity they are supposed to play an important role in B cell repertoire shaping (forming an idiotypic network), through interaction with a broad spectrum of immunological components they act as regulatory molecules, and through their participation in catabolic events they can promote morphogenetic changes during fetal development. Beneficial therapeutic effects of nonspecific gammaglobulin (IVIG) application observed recently in patients with autoimmune diseases suggest that they can influence autoimmune reactivity by a not yet analyzed mechanism. Other functions of natural autoantibodies can be suggested and expected to be found in the near future.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: sliznice; Immunity, Innate; Autoimmunity; přirozená imunita; B-lymfocyty; B-Lymphocytes; autoimunita; Mucous Membrane